The Effect of Audit Opinion and Audit Committee on Audit Delay with The Reputation of The KAP as Moderating - Umami, Akmalludin; Rosharlianti, Zulfa (EAJ (Economic and Accounting Journal), 2021)
This study aims to determine whether the Audit Opinion and the Audit Committee will affect the Audit Delay. And whether the KAP's reputation is able to moderate the Audit and Audit Committee's Opinion on Audit Delay. This study also involves independent variables, namely Audit Opinion and the Audit Committee. And also involves a moderating variable, namely the reputation of the hood. The type of research used in this research is associative research with a quantitative approach. The data collection technique in this study is secondary data with data collection methods, namely documentation. The study was conducted on 40 property and real estate sector companies listed on the Indonesia Stock Exchange in 2016-2020. Based on the test results, it proves that the Audit Opinion and the Audit Committee have a simultaneous effect on Audit Delay. This study also proves that audit opinion can affect audit delay, while audit committee has no effect on audit delay. This study also shows the results that the reputation of the company is able to moderate audit opinion on audit delays. The reputation of the KAP is not able to moderate the influence of the audit committee on the audit delay.